A Conservative Approach to Inflammatory Myofibroblastic Tumor of the Bladder: A Case Report and Review of Literature - Rawad Abou Zahr; Elie Ghabi; Mehdi Idrissi-Kaitouni; Thierry Roumeguere (Case Reports in Urology)
Inflammatory myofibroblastic tumors (IMTs) are particularly rare tumors that have been described in various anatomic locations, of which the urinary bladder is the most common. These benign tumors are amendable to conservative therapy but are notoriously difficult to diagnose given their mimicry of malignant sarcomas and sarcomatoid carcinomas, making an accurate diagnosis paramount to spare a patient radical and unnecessary treatment. We hereby present the case of a 37-year-old female patient who was diagnosed with an IMT of the urinary bladder during workup for painless gross hematuria. Patient was successfully managed with a laparoscopic partial cystectomy and is free of recurrence 5 years after surgery. IMTs are rare benign tumors that share the same clinical presentation as malignant bladder tumors. Deep biopsy and experienced pathologist are crucial in establishing diagnosis and avoiding patient radical treatment. This case is a classical demonstration of a remarkably rare tumor that was adequately managed with conservative therapy, achieving excellent clinical outcomes.